Decisive role of mixed‐valence structure in colossal dielectric constant of LaFeO3. Issue 7 (10th April 2017) - Ni, Wei; Ye, Jianglin; Guo, Youmin; Cheng, Chao; Lin, Zhongqin; Li, Yide; Wang, Hong; Yu, Yi; Li, Qiuju; Huang, Shouguo; Shao, Zongping; Wang, Chunchang
Abstract: The role of mixed‐valence structure in colossal dielectric constant (CDC) behavior has been investigated in LaFeO3 ceramics by tuning the ratio of Fe 2+ /Fe 3+ through substituting Al for Fe. The ratio of Fe 2+ /Fe 3+ is decreased gradually from 1.0 to 0.0 by increasing the concentration of Al 3+ . Two clear‐cut correlations have been found: (i) the relationship between the CDC behavior and the ratio of Fe 2+ /Fe 3+ follows an exponential function and (ii) the activation energy of the polaron relaxation is proportional to 1 / ε 0 2, where ε 0 is the intrinsic dielectric constant. These findings underscore the role of the mixed‐valence structure in CDC behavior and suggest that adjusting the mixed‐valence structure through doping/alloying can be a promising strategy to achieve superior CDC behavior in transition‐metal oxides.